Retail Consumers Market in India - The Next Big Leap - Anbalagan, M.; Gunasekaran, V. (Indian Journal of Marketing, 2006)
Liberalization and a steady economic growth have driven a vast change in India. Till a few years ago, the Indian consumer was content with one channel of television - Doordarshan, a few retail stores in every city, one large national footwear chain - Bata, and the showrooms of various mills that retailed fabric. The scene is very different today, with malls, lifestyle stores, department stores and specialty stories, all vying for the customer’s attention. In a short span of a little over ten years, the market dynamics have changed phenomenally. The person driving this change is the consumer.India has been a nation of Dukandars - around 12 million retailers, more retail shops than the rest of the world put together. Retailing has been in our blood - as a shopkeeper or as a shopper. The business of retail in India has seen significant changes in the last few years. We have seen the emergence of new formats and the application of global concepts and constructs albeit with modifications to suit the Indian environment. It not only provides the Indian consumer a wide choice, but also represents a very large employment opportunity for people with diverse skill sets. Therefore this paper highlights the growth, demographic and consumer behavior, opportunities, challenges and emerging trends in retail consumer market.